Populism, authoritarianism, and charismatic-plebiscitary leadership in contemporary Asia: a comparative perspective from India and Myanmar. Issue 5 (20th October 2021) - Subedi, D. B.; Scott, Alan
ABSTRACT: Much of the revived interest in new – populist and/or authoritarian – styles of leadership has been a response to developments, initially in Europe, from the late1980s on, one aspect of which has been a renewed interest in charisma and in plebiscitary leadership. How applicable are approaches to leadership developed primarily in European political science and sociology to contemporary South and Southeast Asia? Building both on Weber's classical account of charismatic authority, and on more recent work, we propose a relational conception of charisma as an interaction between leader and followers. This leader-follower dialectic is a key characteristic of contemporary populist politics. In order to investigate the ways in which populist leaders appeal to followers, we apply this relational conception of charisma to two Asian national cases: India under Narendra Modi and Myanmar under Aung San Suu Kyi during the – now arrested – period of transition from military rule. We shall be primarily concerned with one specific form of charisma: plebiscitary leadership.